Desain Laboratorium Pembelajaran IPS pada Program Studi Tadris IPS - Purwanto, Iwan (Sosio-Didaktika: Social Science Education Journal, 2023)
The laboratory is an important infrastructure that must be owned by the Social Sciences Tadris Study Program. The laboratory is important for prospective Social Sciences teachers in improving their ability to carry out learning in the laboratory room and at the same time improving the management skills of Social Sciences learning laboratories. However, the laboratories at Educational Institutions and Education Personnel (LPTK) are generally synonymous with biology, chemistry, physics, language, and computer laboratories, while social studies learning laboratories are not widely owned and there is no standard laboratory design. Therefore this study aimed to produce a social studies learning laboratory design in the Social Sciences Tadris Study Program, Faculty of Tarbiyah and Teaching Sciences (FITK) UIN Syarif Hidatullah Jakarta. The research method used is Research-Based Design (RBD) with the research stages (1) contextual inquiry; (2) participatory design; (3) preliminary design; (4) conceptual design or prototype design (conceptual design/prototype as a hypothesis). Respondents in this study were student, laboratory assistants, laboratory assistants, and lecturers at FITK. Data is taken through a rubric that must be filled in about learning activities or practice in the laboratory and through interviews. The results of this study are the design of social studies learning laboratories with 3 laboratory rooms, namely (1) a practice room for storing tools and materials; (2) a preparation room and laboratory assistant; (3) waiting and guest rooms.